2014
DOI: 10.1039/c4cc01457j
|View full text |Cite
|
Sign up to set email alerts
|

Controlling nucleation in giant liposomes

Abstract: We introduce giant liposomes to investigate phase transformations in picoliter volumes. Precipitation of calcium carbonate in the confinement of DPPC liposomes leads to dramatic stabilization of amorphous calcium carbonate (ACC). In contrast, amorphous strontium carbonate (ASC) is a transient species, and BaCO3 precipitation leads directly to the formation of crystalline witherite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 33 publications
2
69
1
Order By: Relevance
“…14,16 Systematic studies of the precipitation of CaCO 3 and CaSO 4 have suggested that there are various mechanisms by which confinement can affect the kinetics of the precipitation. The considerable stabilization observed for amorphous calcium carbonate (ACC) within unilamellar vesicles 17,19 has been attributed to the exclusion of nucleating impurities from these small volumes. An alternative mechanism was proposed to explain the observed stabilization of ACC with respect to calcite in the crossed-cylinder apparatus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,16 Systematic studies of the precipitation of CaCO 3 and CaSO 4 have suggested that there are various mechanisms by which confinement can affect the kinetics of the precipitation. The considerable stabilization observed for amorphous calcium carbonate (ACC) within unilamellar vesicles 17,19 has been attributed to the exclusion of nucleating impurities from these small volumes. An alternative mechanism was proposed to explain the observed stabilization of ACC with respect to calcite in the crossed-cylinder apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has provided strong evidence, however, that confinement can also have significant effects on the precipitation of compounds such as calcium carbonate 13 and calcium sulfate, sometimes at surprisingly large length scales. [14][15][16][17][18][19] In this article, we investigate the effects of confinement on the precipitation of calcium phosphate (CaP), the principal inorganic component of bones and teeth. Confinement plays a key role in the formation of bone, which begins with the growth of ultrathin platelets of nonstoichiometric carbonated hydroxyapatite (HAP) within gaps in the collagen fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning probe microscopy is of little use, for example, in examining crystallization pathways that involve aggregation or ordered assembly of molecular clusters [7] or post-nucleation particles [8,9] in bulk solutions. Similarly, nucleation events that occur within ScienceDirect organic matrices, such as globular phases of macromolecules [10], lipid vesicles [11,12], amelogenin [13], and collagen [14], cannot be accessed via scanned probe methods.…”
Section: Introductionmentioning
confidence: 98%
“…Where the pore surface is wetted by the nucleus, nucleation rates should be enhanced over those on flat substrates for pore dimensions on the order of the critical nucleus size, because the curvature of the pore enables a larger fraction of the nucleus to be in contact with the substrate. However, dramatic effects on the stability of metastable phases within confined volumes that are orders of magnitude larger than the length scale expected for the critical nucleus have been reported for solutions confined between crossed cylinders (71,93) and in liposomes (72,94). [The latter may be representative of sea urchin embryos (95).]…”
Section: Effect Of Extrinsic Factors: Surfaces Impurities and Confimentioning
confidence: 99%